Notes on the genus Metaeuchromius Bleszynski (Lepidoptera: Crambidae: Crambinae) from China, with description of two new species - Li, Weichun; Li, Houhun; Nuss, Matthias (Zootaxa, 2009)
The genus Metaeuchromius Bleszynski is studied in China, with four species treated in this paper. Metaeuchromius singulispinalis sp. nov. and M. anacanthus sp. nov. are described as new; M. inflatus Schouten, 1997 is newly recorded for China; and the female of M. flavofascialis Park, 1990 is described for the first time. Images of the adults and genitalia are provided, along with keys to all the known species based on male and female genitalia.